Genetic modifiers of Hb E/β0 thalassemia identified by a two-stage genome-wide association study - Winichagoon Pranee; Makarasara Wattanan; Angkachatchai Vach; Whitacre Johanna; Ma Qianli; Abel Kenneth; Sripichai Orapan; Sherva Richard; Svasti Saovaros; Fucharoen Suthat; Braun Andreas; Farrer Lindsay A (BMC, 2010)
Abstract Background Patients with Hb E/β0 thalassemia display remarkable variability in disease severity. To identify genetic modifiers influencing disease severity, we conducted a two-stage genome scan in groups of 207 mild and 305 severe unrelated patients from Thailand with Hb E/β0 thalassemia and normal α-globin genes. Methods First, we estimated and compared the allele frequencies of approximately 110,000 gene-based single nucleotide polymorphisms (SNPs) in pooled DNAs from different severity groups. The 756 SNPs that showed reproducible allelic differences at P < 0.02 by pooling were selected for individual genotyping. Results After adjustment for age, gender and geographic region, logistic regression models showed 50 SNPs significantly associated with disease severity (P < 0.05) after Bonferroni adjustment for multiple testing. Forty-one SNPs in a large LD block within the β-globin gene cluster had major alleles associated with severe disease. The most significant was bthal_bg200 (odds ratio (OR) = 5.56, P = 2.6 × 10-13). Seven SNPs in two distinct LD blocks within a region centromeric to the β-globin gene cluster that contains many olfactory receptor genes were also associated with disease severity; rs3886223 had the strongest association (OR = 3.03, P = 3.7 × 10-11). Several previously unreported SNPs were also significantly associated with disease severity. Conclusions These results suggest that there may be an additional regulatory region centromeric to the β-globin gene cluster that affects disease severity by modulating fetal hemoglobin expression.